2015
DOI: 10.1186/s13148-015-0090-4
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic mechanisms of endothelial dysfunction in type 2 diabetes

Abstract: The development of type-2 diabetes mellitus (T2DM) and its complications is largely due to the complex interaction between genetic factors and environmental influences, mainly dietary habits and lifestyle, which can either accelerate or slow down disease progression. Recent findings suggest the potential involvement of epigenetic mechanisms as a crucial interface between the effects of genetic predisposition and environmental factors. The common denominator of environmental factors promoting T2DM development a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
65
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(67 citation statements)
references
References 117 publications
(127 reference statements)
0
65
0
2
Order By: Relevance
“…Interestingly, in contrast to blood miR-126, our meta-analyses showed that urinary miR-126 excretion was significantly increased in patients with DN, although there was a significant heterogeneity. This discrepancy may indicate either a local kidney-specific role or compensatory increases in VEGF and miR-126 in the pathogenesis and/or progression of DN involving microvascular endothelial cells [36, 37]. …”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in contrast to blood miR-126, our meta-analyses showed that urinary miR-126 excretion was significantly increased in patients with DN, although there was a significant heterogeneity. This discrepancy may indicate either a local kidney-specific role or compensatory increases in VEGF and miR-126 in the pathogenesis and/or progression of DN involving microvascular endothelial cells [36, 37]. …”
Section: Discussionmentioning
confidence: 99%
“…1). 41,42 Activation of the NF-kB pathway, in turn, induces monocytes/ macrophages and endothelial cells production of several cytokines, including TNF-a, IL-1, IL-6, and adhesion molecules, such as vascular cell adhesion molecule-1 (VCAM-1). 41,42 The association of diabetes, inflammation, and epigenetic changes has been reported also in humans.…”
Section: B-cell Development and Functionmentioning
confidence: 99%
“…41,42 Activation of the NF-kB pathway, in turn, induces monocytes/ macrophages and endothelial cells production of several cytokines, including TNF-a, IL-1, IL-6, and adhesion molecules, such as vascular cell adhesion molecule-1 (VCAM-1). 41,42 The association of diabetes, inflammation, and epigenetic changes has been reported also in humans. A recent study on adipose tissue from monozygotic twins discordant for T2DM (diabetics vs. non-diabetics) reported increased expression of inflammatory genes, such as secreted phosphoprotein (SPP)1 (also known as osteopontin, OPN), chemokine (C-C motif) ligand (CCL)18 and IL1RN, in association with variations of global and localized DNA methylation.…”
Section: B-cell Development and Functionmentioning
confidence: 99%
“…Promoter hypermethylation of tumour suppressor genes is a kind of epigenetic mechanisms in cancer cells [22]. Epigenetic modifications have been shown to be crucial mediators underlying in miRNA down-regulation and to display a tight correlation with carcinogenesis [16, 23]. Our data demonstrated that the hypermethylation of the upstream promoter of miR-507 led to the down-regulation of miR-507 in breast-cancer tissues and cell lines.…”
Section: Discussionmentioning
confidence: 63%